THE EFFECT OF USING THEMATIC LEARNING MODELS ON THE LEARNING OUTCOMES OF CLASS IV ELEMENTARY SCHOOL - Sri Utami (Sensei International Journal of Education and Linguistic, 2021)
This study aims to determine the effect of using thematic models on student learning outcomes on the theme of the beauty of diversity in Negeri Ku in the fourth grade of SD Negeri Padang Panyang, Kuala Pesisir District, Nagan Raya Regency. This study used the Quasi Experiment Design method with the research design Nonequivalent control group design. Samples were selected randomly. The population of this research was all class IV SD Negeri Padang Panjang with a sample of class IV B totaling 25 students as the control class and class IVA totaling 24 students as the experimental class. The data collection technique used a written test. The data analysis technique used the t-test. The results showed that the post-test results of the control class learning outcomes were 61.44 and the experimental class 76.83 and gradest_hitung5,773> that is 2.01174. This means that there is a significant difference between the post-test results of the experimental class using the thematic learning model and the control class using the lecture method. So it can be concluded that there is influencet_tabelThe Use of Thematic Models of Student Learning Outcomes on the theme of the beauty of diversity in Negeri ku in Class IV SD Negeri Padang Panjang, Kuala Pesisir District, Nagan Raya Regency.